Competition Law and Policy in Latin America. - Fox, Eleanor M. (Hart Pub., 2009)
This book offers an unparalleled analysis of the emerging law and economics of competition policy in Latin America. Nearly all Latin American countries now have competition laws and agencies to enforce them. Yet, these laws and agencies are relatively young. The relative youth of Latin American competition agencies and the institutional and political environment in which they operate limit the ability of agencies to effectively address anti-competitive conduct. Competition policy is a tool to overcome anti-market traditions in Latin America. Effective competition policy is critical to assistin.